Distribusi Kekayaan Dalam Pemikiran Muhammad Baqir Al-Sadr: Solusi Untuk Keadilan Sosial di Era Kontemporer - Luthfy Arwiya; Malahayatie (Journal Of Islamic Economics And Finance, 2025)
One of the main problems facing many countries, including Indonesia, is the growing income gap. To address this imbalance, Muhammad Baqir al-Sadr's economic thought provides a relevant paradigm of wealth distribution. Al-Sadr, who based his arguments on Islamic principles, highlighted the role of zakat, waqf, and the prohibition of usury in establishing social justice. Examining al-Sadr's thoughts on wealth distribution and its application to the Indonesian economy in the contemporary era is the purpose of this article. Using the literature study research method, According to this study, Islamic economic thought developed by Muhammad Baqir al-Sadr provides an alternative to the traditional economic system, particularly through the idea of Iqtiṣādunā. This idea highlights the principle of balanced ownership between individuals and society, the role of the state in the economy, and the equitable distribution of wealth. Within an economic framework based on social justice and inclusive ownership, this concept can improve social welfare and reduce economic inequality in Indonesia if implemented properly.